2021
DOI: 10.15244/pjoes/134540
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic Fungi Controls the Physicochemical Status of Maize Crop under Salt Stress

Abstract: Salt stress is one of the abiotic stresses which negatively affects the growth and yield of different plants world-wide. The purpose of the present investigation was to analyze the physiological and biochemical parameters of maize plants exposed to salt stress with or without fungal association. The results indicated that salinity negatively affected the growth attributes, biochemical parameters and ionic status in maize. In contrast, WSQ association has improved the growth parameters, antioxidant enzyme activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…Previously, the endophytic association of A. awamori increased the level of carbohydrates in mung bean plants under both controlled and salt-stressed conditions. The increased level of soluble sugars in salt stress in A. awamori -associated mung bean could be attributed to molecular defense against oxidative damage (Ali et al, 2022 ). The association of B. subtilis combined with AMF has previously affected the activity of enzymes such as nitrate reductase and nitrite reductase under salinity resulting in increased nitrogenase activity.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previously, the endophytic association of A. awamori increased the level of carbohydrates in mung bean plants under both controlled and salt-stressed conditions. The increased level of soluble sugars in salt stress in A. awamori -associated mung bean could be attributed to molecular defense against oxidative damage (Ali et al, 2022 ). The association of B. subtilis combined with AMF has previously affected the activity of enzymes such as nitrate reductase and nitrite reductase under salinity resulting in increased nitrogenase activity.…”
Section: Discussionmentioning
confidence: 99%
“…According to Alen'kina and Nikitina ( 2020 ), plants under salt stress showed an increase in ascorbate peroxidase activity. SOD, peroxidase (POD), and catalase (CAT) activity were all higher in endophyte-colonized plants, implying that the coordination of POD and CAT activity, as well as SOD activity, played a key role in the O 2− and H 2 O 2 scavenging process (Ali et al, 2022 ). The current study also showed that inoculating maize plants with S. lycopersici improved the activity of antioxidant enzymes (catalase and ascorbate peroxidase) and the level of lipid peroxidation in both salinity and normal environments.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations